Gas Hold-Up Profiles Determination by means of Ultrasonic Transducer - Mohd Hafiz, Fazalul Rahiman; Ruzairi, Abdul Rahim; Herlina, Abdul Rahim; Zulkarnay, Zakaria; Muhammad Jaysuman, Pusppanathan; Chiew, Loon Goh; Nasarudin, Ahmad; Yasmin, Abdul Wahab; Fazlul, Rahman (Universiti Teknologi Malaysia, 2014)
This paper details a work carried out to measure gas hold-up profiles in a liquid column using a pair of ultrasonic transducer. The gas hold-up profiles from 1.85 mm to 7.7 mm diameter are of interest in this investigation. The measurement setup consist of ultrasonic transducer, an experimental column, signal conditioning circuit, and a digital storage oscilloscope. The experiment was conducted using several gas hold-up profiles and the relationship between the ultrasonic amplitude and the profile were deduced. A finite element analysis was carried out to further verify the results. This paper explains how one could use ultrasonic transducer to estimate the gas hold-up profiles in a liquid column.